Intraspecific differences in leaf decomposition and associated traits in closely related Carex species: a microcosm experiment - Neumann, Szilvia Márta; Segrestin, Jules; Konečná, Marie; Lisner, Aleš; Applová, Markéta; Blažek, Petr; E-Vojtkó, Anna; Janíková, Eva; Götzenberger, Lars; Lepš, Jan (Oecologia, 2025)
Litter decomposition is a fundamental process in carbon and nutrient cycling in terrestrial ecosystems. In a microcosm experiment we investigated the determinants of leaf decomposition with consideration of the 'afterlife' effect hypothesis, which suggests a connection between green leaf traits and the decomposability of leaf material. We collected senesced litter and living leaves of individuals of four Carex species widely distributed in the Czech Republic. We aimed to determine the extent of intra- and interspecific variability in decomposition rates (k values), whether species ranking was consistent along environmental gradients and whether intraspecific trait variability affected litter decomposability, as we would expect from the 'afterlife' effect hypothesis. While litter quality and decomposition rates significantly differed between fresh leaves and litter, species identity explained a prominent amount of variability in both. The effect of populations was around a tenth of species identity's, nonetheless still significant. Environmental variables and leaf traits generally showed rather weak or non-significant correlations with decomposition rates, which suggests that within closely related species ecological preferences might not be correlated with leaf decomposability, nor the conditions of individual localities are modifying tissue quality in a way to affect decomposability. While the correlation between fresh leaf and litter decomposition rates was not very strong (r = 0.51), fresh leaves provided a fair prediction of litter decomposition. However, considering the pattern of intra- and interspecific differences in decomposition rates, and the quality of fresh leaves and litter, using litter to determine leaf decomposability might give more realistic results.
Keywords: Česká republika; listy rostlin; Afterlife; Carex (rostlina); ekosystém; Czech Republic; druhová specificita; Environmental preferences; Intraspecific variability; Litter quality; Leaf traits; Carex Plant; Ecosystem; Species Specificity; Plant Leaves